How to divide the pancreatic parenchyma in patients with a portal annular pancreas: laparoscopic spleen-preserving distal pancreatectomy for serous cystic neoplasms - Naohisa Kuriyama; Tomohide Hatanaka; Kazuaki Gyoten; Aoi Hayasaki; Takehiro Fujii; Yusuke Iizawa; Hiroyuki Kato; Yasuhiro Murata; Akihiro Tanemura; Masashi Kishiwada; Hiroyuki Sakurai; Shugo Mizuno (Surgical Case Reports)
Abstract Background Portal annular pancreas (PAP) is a rare pancreatic anomaly in which the uncinate process wraps annularly around the portal vein and fuses to the body of the pancreas. PAP is highly relevant to the development of postoperative pancreatic fistula (POPF) in pancreatic surgery. Here, we describe our experience and surgical technique of laparoscopic spleen-preserving distal pancreatectomy using Warshaw’s procedure for patients with the PAP. Case presentation A 49-year-old woman with PAP was referred to our hospital for a suspicious mucinous cystic neoplasms 1.5 cm in diameter in the pancreatic tail. Laparoscopic spleen-preserving distal pancreatectomy using Warshaw’s procedure was performed. Mobilization of the pancreatic tail was first performed, and then, the splenic artery was cut. After dividing the pancreatic tail from the splenic hilum, the ventral pancreatic parenchyma was divided using a stapler. After cutting the splenic vein, complete mobilization of the pancreatic body and tail enabled easy division of the PAP. Finally, the PAP was also divided using the stapler. Although grade B POPF occurred, she was discharged on the 9th postoperative day. Conclusions Surgeons should understand the anatomical characteristics of PAP and be aware of the possibility of POPF.